Effect size of delayed freezing, diurnal variation, and hindgut location on the mouse fecal microbiome - Kevin L. Gustafson; Zachary L. McAdams; Amber L. Russell; Rebecca A. Dorfmeyer; Giedre M. Turner; Aaron C. Ericsson (iScience, 2024)
Summary: Practical considerations in fecal sample collection for microbiome research include time to sample storage, time of collection, and hindgut position during terminal collections. Here, parallel experiments were performed to investigate the relative effect of these factors on microbiome composition in mice colonized with two different vendor-origin microbiomes. 16S rRNA amplicon sequencing of immediately flash-frozen feces showed no difference in alpha or beta diversity compared to samples incubated up to 9 h at room temperature. Samples collected in the morning showed greater alpha diversity compared to samples collected in the afternoon. While a significant effect of time was detected in all hindgut regions, the effect increased from cecum to distal colon. This study highlights common scenarios in microbiome research that may affect outcome measures of microbial community analysis. However, we demonstrate a relatively low effect size of these technical factors when compared to a primary experimental factor with large intergroup variability.